Air Disinfection-From Medical Areas to Vehicle - Anna Bukłaha; Anna Wieczorek; Ewelina Kruszewska; Piotr Majewski; Dominika Iwaniuk; Paweł Sacha; Elzbieta Tryniszewska; Piotr Wieczorek (Frontiers Media S.A., 2022)
Cars with air conditioning systems have become the norm, but these systems can be dangerous for human health as a result of the accumulation of different microorganisms, including pathogenic ones, causing severe allergy or inflammation problems. The novel purpose of this study is 2-fold: on the one hand, to test different disinfection agents on a new area, that is, automobile cabins, and on the other, to compare activity in the gas phase of these agents for disinfection of car air conditioning and cabin surfaces. This study shown that tested disinfectant agents dedicated for decontamination medical areas (agent based on peracetic acid and an agent containing didecyldimethylammonium chloride, 2-phenoxyethanol with cinnamaldehyde) can be successfully used for disinfection car air conditioning and cabin surfaces. Both disinfectants were examined in comparison to a commercial "ready-to-use" spray from a local supermarket dedicated to car air conditioning disinfection. Our research found that very effective agents in this regard were acid stabilized by hydrogen peroxide applied by fumigator, and a combination of didecyldimethylammonium chloride, 2-phenoxyethanol, and cinnamaldehyde applied by atomizer. Tested disinfection procedures of car air conditioning significantly influence the quality of cabin air and surfaces by reducing the amount of microorganisms. The comparison of disinfection properties studied agents in the gas phase reveal statistically significant differences between it effect for disinfection car air conditioning and cabin surfaces. Our research found that very effective agents in this regard were acid stabilized by hydrogen peroxide applied by fumigator, and a combination of didecyldimethylammonium chloride, 2-phenoxyethanol, and cinnamaldehyde applied by atomizer. Tested disinfection procedures of car air conditioning significantly influence the quality of cabin air and surfaces by reducing the amount of microorganisms.